The Concept of Nonviolence in the Political Theology of Martin Luther King - Brzechczyn, Krzysztof (Wydawnictwo Naukowe UAM, 2004)
This article presents the political theology of Martin Luther King. I analyze the notion of political theology, King's argumentation in favour of non-violence strategy in politics and reconstruct a standard model of non-violence action. Finally, I discuss some philosophical and political controversies arising around passive resistance.
Keywords: Martin Luther King; political theology; United States; non-violence; baptism; Gandhi